A method for measuring the phase transition temperature of low alloy steel during continuous cooling and a method for regulating its mechanical properties
The phase transition process of low alloy steel is observed in situ by a high-temperature metallographic microscopy system, combined with software analysis and continuous cooling experiments, the problem of difficult to determine the phase transition temperature and type of low alloy steel in the prior art is solved, and the optimization of the heat treatment process and the regulation of material performance is achieved.
Patent Information
- Application Number
- CN202411989116.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to quickly and accurately determine the phase transition temperature, phase transition type and phase transition degree of continuous cooling of low alloy steel, resulting in the inability to optimize the heat treatment process and regulate the performance of low alloy steel.
The high-temperature metallographic microscopy system was used to observe the solid/liquid phase changes of low alloy steel or the alloy microstructure phase changes in in situ. The phase transition type and degree of phase transition were obtained by software analysis of the images, and the CCT curve was obtained through continuous cooling experiments.
It realizes intuitive understanding and accurate evaluation of the phase change process of low alloy steel, optimizes the heat treatment process, improves product quality and yield, and simplifies the operation process.
Smart Images

Figure CN119757452A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phase change temperature determination, and in particular to a method for measuring the continuous cooling phase change temperature of low alloy steel and a method for regulating and controlling its mechanical properties. Background Art
[0002] In the field of materials science and engineering, especially in the field of metal heat treatment, the determination of phase transition temperature is an important research direction. Phase transition temperature refers to the temperature at which a substance changes from one state to another, which is of great significance for understanding the performance and application of materials. In actual production, accurately determining the continuous cooling phase transition temperature of low alloy steel plays an important role in optimizing heat treatment processes and improving product quality.
[0003] However, due to the complexity and invisibility of the phase change process of low alloy steel, it is difficult to determine the phase change type and accurately measure the phase change temperature. The existing phase change temperature determination technology mainly determines the phase change temperature through experimental methods, such as differential scanning calorimetry (DSC), thermal expansion method, etc.; although these methods can provide certain phase change information, they cannot intuitively display the phase change type, nor can they accurately determine the phase change degree, and cannot obtain the precise phase change temperature, which makes it impossible for us to intuitively understand the phase change process and accurately evaluate the effect of heat treatment, and thus it is impossible to accurately control the phase change process. In addition, these existing methods usually require complex equipment and long testing time, which is not conducive to practical application.
[0004] Therefore, how to accurately determine the continuous cooling phase transition temperature of low alloy steel is an urgent problem to be solved in the current field of metal material analysis technology. Summary of the invention
[0005] In view of the above analysis, an embodiment of the present invention aims to provide a method for measuring the phase transition temperature of continuous cooling of low alloy steel and a method for regulating its mechanical properties, so as to solve at least one of the problems that the prior art cannot quickly and accurately determine the phase transition temperature, phase transition type and phase transition degree of continuous cooling of low alloy steel to optimize the heat treatment process and regulate the performance of low alloy steel.
[0006] In one aspect, an embodiment of the present invention provides a method for determining a continuous cooling phase transition temperature of low alloy steel, the method comprising:
[0007] (1) Preparation of low alloy steel samples;
[0008] (2) placing the sample in a heating device of a high-temperature metallographic microscope system for heating treatment and in-situ microstructure observation;
[0009] (3) subjecting the sample to continuous cooling treatment and in-situ observation;
[0010] (4) Importing the images collected in step (2) and step (3) into the software, the phase change type and the percentage of each phase are obtained by binary method and calibration method.
[0011] Furthermore, in step (2), the magnification of the high temperature metallographic microscope is 250-2000 times, the image acquisition resolution is 1024*1024 pixels, and the image acquisition number is 1-50 frames / second.
[0012] Furthermore, in the step (2), the sample is heated to above the austenitizing temperature, and the heating rate is 1-20°C / s.
[0013] Furthermore, in step (2), before subjecting the sample to a temperature-raising heat treatment, the method further includes: introducing argon and helium into the high-temperature metallographic microscope system and evacuating the system, and performing a cycle of 3-5 times.
[0014] Furthermore, in step (3), the continuous cooling temperature is 0.03-100°C / s, preferably 20°C / s, 10°C / s, 5°C / s, 1°C / s, 0.3°C / s, 0.15°C / s, 0.1°C / s, 0.05°C / s, 0.03°C / s.
[0015] Furthermore, in step (1), the sample preparation method includes: processing a low alloy steel cylindrical sample, grinding, polishing, cleaning and drying.
[0016] Furthermore, in step (4), the phase transformation type is alloy solid / liquid phase and / or alloy microstructure phase.
[0017] Furthermore, the alloy microstructure phase is one or more of pearlite, bainite and martensite.
[0018] Furthermore, the method further comprises performing a mechanical property test, preferably a hardness test, on the sample after the continuous cooling treatment in step (3).
[0019] Furthermore, in terms of mass percentage, the composition of the low alloy steel includes: C 0.05-0.25%, Si 0.15-0.5%, Mn 0.3-1.5%, Cu<0.05%, Ni 0.25-1.0%, Cr0.25-1%, Nb 0.02-0.15%, V 0.02-0.15%, Al<0.1%, Ti 0.02-0.15%, Mo 0.15-0.5%, B<0.003%, P<0.015%, S<0.015%, N<0.025%, and the rest is Fe.
[0020] On the other hand, an embodiment of the present invention provides a method for regulating the mechanical properties of low alloy steel, wherein the method comprises the above-mentioned method for determining the continuous cooling phase transition temperature of low alloy steel.
[0021] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0022] 1. The present invention uses a high-temperature metallographic microscope system to in-situ observe the solid / liquid phase change or / and alloy microstructure phase change of low alloy steel during heat treatment, which can not only visually and intuitively determine the phase change type, but also can use software to perform organizational analysis on the images collected in-situ, calibrate and calculate the phase ratio at different temperatures, and quantify the phase change or microstructure change, so as to more accurately determine the phase change type, phase change temperature and phase change degree of the alloy at different heat treatment temperatures; at the same time, through data analysis technology, the results of the continuous cooling experiment are statistically analyzed and analyzed to obtain the CCT curve of the low alloy steel at a constant continuous cooling rate, such as Fig.11 As shown, the results are basically consistent with the traditional thermodynamic calculation values.
[0023] The method of the present invention enables intuitive understanding of the phase change process and accurate evaluation of the effect of heat treatment, which is conducive to accurately guiding and controlling the phase change process; the method requires simple equipment and short testing time, and the observation and recording of the phase structure of the sample can be completed during the heat treatment process, and the measurement can be completed in situ. Compared with the prior art, the operation process is greatly simplified.
[0024] 2. The present invention heats the low alloy steel to a temperature above the austenitizing temperature, or even higher than the melting temperature of the alloy, and maintains the temperature for a period of time to ensure that in-situ images of the transformation between various alloy microstructures can be collected during the subsequent continuous cooling process, and even in-situ images of the process of liquid alloy solidifying into a solid state can be collected. The quantitative analysis of the alloy phase change can be achieved through the organizational analysis of the in-situ images by software.
[0025] 3. The present invention controls the continuous cooling rate within the range of 0.03-100°C / s to cover the cooling rate range that can be obtained by current cooling technology. Through the tissue analysis of in-situ images, the phase change process can be understood more comprehensively and accurately to better optimize the heat treatment process or guide the design of new materials that meet special environments and performance requirements.
[0026] 4. The present invention records the phase changes of low alloy steel during continuous cooling in situ through microscopic imaging technology, and controls the image acquisition effect and the accuracy of phase change temperature determination by adjusting the number of images collected per second and the magnification of the microscope objective lens; multiple groups of identical samples are continuously cooled at a constant speed, and the cooling speed of each group of samples is different. Multiple groups of parallel experiments are performed, and the continuous cooling transformation phase diagram of low alloy steel can be obtained according to the results of the multiple groups of experiments, thereby obtaining the change of phase change temperature in the continuous cooling process with the continuous cooling speed.
[0027] In addition, the method of the present invention also conducts mechanical property tests on the samples obtained after continuous cooling, and establishes a correspondence between the material phase change type and phase change degree and the alloy performance test results. Through this correspondence, the heat treatment process parameters of low alloy steel can be selected according to actual needs, thereby promoting the regulation of the mechanical properties of low alloy steel and the development of new materials.
[0028] 5. Compared with the existing experimental methods, the method of the present invention uses simple equipment, is easy to operate, has a short test time, and is more conducive to practical application. Through the method of the present invention, in the actual application process, the heat treatment process of low alloy steel can be guided, product defects can be reduced, and heat treatment efficiency and yield can be improved.
[0029] 6. The method of the present invention can be expanded to optimize the heat treatment process of other metals or alloys.
[0030] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0032] Figure 1 The microscopic photographs of the solid / liquid phase of low alloy steel I at different temperatures during the heat treatment process of Example 1 and the quantitative analysis results of the liquid phase are as follows: (a) is the heating process; (b) is the cooling process;
[0033] Figure 2 The microstructure photos and the quantitative analysis results of martensite of the alloy at different temperatures during the continuous cooling process at a rate of 20°C / s in Example 2;
[0034] Figure 3The microstructure photos and the quantitative analysis results of martensite of the alloy at different temperatures during the continuous cooling process at a rate of 10°C / s in Example 3;
[0035] Figure 4 The microstructure photos and the quantitative analysis results of martensite of the alloy at different temperatures during the continuous cooling process at a rate of 5°C / s in Example 4;
[0036] Figure 5 The microstructure photos and the quantitative analysis results of martensite of the alloy at different temperatures during the continuous cooling process at a rate of 1°C / s in Example 5;
[0037] Figure 6 The microstructure photos of the alloy at different temperatures and the quantitative analysis results of bainite during the continuous cooling process at a rate of 0.3°C / s in Example 6;
[0038] Figure 7 The microstructure photos of the alloy at different temperatures and the quantitative analysis results of bainite during the continuous cooling process at a rate of 0.15°C / s in Example 7;
[0039] Figure 8 The microstructure photos of the alloy and the quantitative analysis results of pearlite at different temperatures during the continuous cooling process at a rate of 0.1°C / s in Example 8;
[0040] Fig. 9 The microstructure photos of the alloy and the quantitative analysis results of pearlite at different temperatures during the continuous cooling process at a rate of 0.05°C / s in Example 9;
[0041] Fig.10 The microstructure photos of the alloy and the quantitative analysis results of pearlite at different temperatures during the continuous cooling process at a rate of 0.03°C / s in Example 10;
[0042] Fig.11 This is the CCT curve of the Q980D alloy obtained in the present invention. DETAILED DESCRIPTION
[0043] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0044] In actual production, accurately determining the continuous cooling phase transition temperature of low alloy steel plays an important role in optimizing heat treatment process and improving product quality. However, due to the complexity and invisibility of the phase transition process of low alloy steel, it is difficult to determine the phase transition type and accurately determine the phase transition temperature.
[0045] The existing phase transition temperature determination technology mainly determines the phase transition temperature through experimental methods, such as differential scanning calorimetry (DSC) and thermal expansion method. Although these methods can provide certain phase transition information, they cannot intuitively display the phase transition type, nor can they accurately determine the phase transition degree, and cannot obtain the precise phase transition temperature, which makes it impossible for us to intuitively understand the phase transition process and accurately evaluate the effect of heat treatment, and thus cannot accurately control the phase transition process. In addition, these existing methods usually require complex equipment and long testing time, which is not conducive to practical application.
[0046] Therefore, the present invention provides a method for measuring the continuous cooling phase transition temperature of low alloy steel, the method comprising:
[0047] (1) Preparation of low alloy steel samples;
[0048] (2) placing the sample in a heating device of a high-temperature metallographic microscope system for heating treatment and in-situ observation;
[0049] (3) subjecting the sample to continuous cooling treatment and in-situ observation;
[0050] (4) Importing the images collected in step (2) and step (3) into the software, the phase change type and the percentage of each phase are obtained by binary method and calibration method.
[0051] Specifically, in order to obtain a sample with a smooth observation surface, the specific process of preparing the low-alloy steel sample in step (1) is as follows: the low-alloy steel sample is cut into the sample required for the experiment, which is generally a cylindrical sample. The cross-sectional size of the sample is determined according to the crucible size, wherein the maximum inner diameter of the crucible is Φ8 mm, and the sample height is 2 mm to 4 mm. In order to prevent the sample size from being too small, resulting in a small selectable field of view, or the sample size from being too large and exceeding the size of the heating crucible, the present invention processes the low-alloy steel into a cylindrical sample of Φ7×4 mm; the surface of the sample obtained after cutting is polished to avoid oxidation and other problems during the cutting process. The material affects the experimental results. Since the sample is small in size and difficult to grind and polish by hand, you can use a special fixture to clamp the sample and then grind it with sandpaper, and polish the surface with a mechanical polisher. The specific method is: after clamping the sample with a fixture, use 60 mesh, 120 mesh, 320 mesh, 600 mesh, 1000 mesh, and 2000 mesh sandpaper to grind the sample in turn. After each sandpaper grinding, the sample needs to be rotated 90 degrees before the next sandpaper grinding, and then use a mechanical polisher to polish the sample. It is recommended to use a polishing agent with a particle size of 0.5-3μm to ensure that the observation surface is clean and scratch-free.
[0052] Further, the processed sample is placed in a crucible, ensuring that the sample has an appropriate height, and is placed in a heating furnace of a high-temperature laser confocal microscope system, and the laser of the microscope is aligned with the center of the sample or the hardness mark point of the sample.
[0053] The inventor found in the study of the heat treatment process of low alloy steel that by using high temperature metallographic microscope technology to observe and analyze the low alloy steel samples in situ during the heating and cooling process of heat treatment, the organizational changes of the samples at different temperatures can be observed intuitively, thereby determining the type of phase change. Compared with traditional optical microscopes and electron microscopes, the high temperature metallographic microscope of the present invention combined with a high-speed CCD camera can achieve high resolution and high magnification real-time imaging, clearly showing the in-situ microstructure of the sample, such as grains, phase boundaries, defects, etc.; it can achieve dynamic organizational observation of materials in the range of -190°C to 1500°C, covering the research temperature range of most metals and alloys; it uses radiation heating to heat the sample, and concentrates on heating the sample at the microscope field of view, and can control the temperature of the experimental sample with high precision, and record the sample temperature in real time through a thermocouple, with an error range of ±1°C to ensure the accuracy of the experiment; it has a vacuum system and an inert gas protection system to prevent the sample from being oxidized during the experiment and interfering with the experimental results.
[0054] Specifically, in step (2), the high temperature metallographic microscope of the present invention can be a laser confocal microscope, a high-power metallographic microscope, a large-depth-of-field digital metallographic microscope, etc.
[0055] According to a preferred embodiment of the present invention, the high temperature metallographic microscope is a high temperature laser confocal microscope.
[0056] Specifically, the present invention controls the magnification of the high-temperature laser confocal microscope to be 250-2000 times, the image acquisition resolution to be 1024*1024 pixels, and the image acquisition number to be 1-50 frames / second, so as to achieve clear and accurate observation and recording of various structures and phase change processes of low-alloy steel during heat treatment, and the objective lens magnification can be switched at any time during the experiment to ensure clear recording of sample changes.
[0057] According to a preferred embodiment of the present invention, the magnification of the high-temperature laser confocal microscope is 500 times and 1000 times, the image acquisition resolution is 1024*1024 pixels, and the image acquisition number is 5 frames / second.
[0058] Furthermore, in order to minimize the oxygen content inside the heating device, in step (2), the present invention performs 3-5 times of vacuuming and ventilation of the high-temperature laser confocal microscope system after sample loading, and each vacuuming and ventilation takes three minutes, wherein the argon flow rate is 200CC and the helium flow rate is more than 6000CC.
[0059] Furthermore, in order to ensure that in-situ images of the transformation between various alloy microstructures can be collected during the subsequent continuous cooling process, and even in-situ images of the process of liquid alloy solidifying into a solid state can be collected, the present invention heats the low alloy steel to above the austenitizing temperature, or even higher than the melting temperature of the alloy, and maintains it for a period of time to ensure complete transformation of the alloy phase.
[0060] Specifically, in step (2), the present invention heats the low alloy steel to above 975° C. at a heating rate of 1-20° C. / s and maintains the temperature for 10-15 minutes.
[0061] According to a preferred embodiment of the present invention, the low alloy steel is heated to 1540° C. and kept at this temperature for 10 minutes, and then heated to 975° C. and kept at this temperature for 15 minutes.
[0062] Specifically, in step (3), the present invention controls the continuous cooling rate of the low alloy steel within the range of 0.03-100°C / s to cover the cooling rate range that can be obtained by current cooling technology. By analyzing the structure of the in-situ image, the phase change process can be understood more comprehensively and accurately to better optimize the heat treatment process, or to guide the design of new materials that meet special environmental and performance requirements.
[0063] Specifically, to prevent oxidation of the sample, an inert gas is used as the cooling gas. Due to the different thermal conductivity properties of the cooling gases, when the cooling rate is lower than 10°C / s, argon cooling is used. When the cooling rate is higher than 10°C / s, helium cooling is required because of its excellent thermal conductivity.
[0064] According to a preferred embodiment of the present invention, the continuous cooling rates are 20°C / s, 10°C / s, 5°C / s, 1°C / s, 0.3°C / s, 0.15°C / s, 0.1°C / s, 0.05°C / s and 0.03°C / s respectively.
[0065] Specifically, during the heating and cooling processes of step (2) and step (3), the sample video images collected in situ are recorded and saved in real time through a high-temperature metallographic microscope.
[0066] It should be noted that the present invention uses a high-temperature metallographic microscope system to in-situ observe the solid / liquid phase changes and / or alloy microstructure phase changes of low alloy steel during heat treatment. It can not only visually and intuitively determine the phase change type, but also use software to perform organizational analysis on the images collected in situ, calibrate and calculate the phase ratios at different temperatures, and quantify the phase changes or microstructure changes, thereby more accurately determining the phase change type, phase change temperature and phase change degree of the alloy at different heat treatment temperatures.
[0067] Specifically, in step (4), the present invention imports the images collected in step (2) and step (3) into the software, and obtains the phase change type and the percentage of each phase through the binary method and calibration method.
[0068] Furthermore, the present invention imports the images collected in step (2) and step (3) into Adobe Premiere software, browses the video images, selects each phase change interval, and exports the selected video images as single-frame photos to determine the phase change type, phase change temperature and phase percentage. The specific method includes: importing the selected photos into Photoshop and Image ProPlus software, and obtaining the phase change type and the percentage of each phase through a binary method and a calibration method.
[0069] Furthermore, for images containing two or fewer microstructures, they were imported into Image Pro Plus software, and the Segmentation module was used to calibrate each phase of tissue using the binary method, and the area percentage of each tissue phase was calculated;
[0070] Furthermore, for images containing three or more microstructures, the images were first imported into Photoshop software, and the object selection tool was used to manually distinguish the multiphase tissues and store the processed images separately, and then imported into Image ProPlus software to calculate the area percentage of each tissue phase;
[0071] Furthermore, for tissue type identification, the microstructure of the tissue can be effectively distinguished by observing the microscopic morphology of the tissue based on the video data obtained from the in-situ test and combining the temperature range and phase transformation rate of the phase transformation. Specifically, the transformation temperature of martensite in low alloy steel is generally around 400°C, and its transformation rate can reach 5×10 -5 to 5×10 -7 The transformation process is generally completed within a few seconds; the bainite transformation temperature is generally between 400-600℃, and its transformation rate is relatively slow; the pearlite transformation temperature is around 700℃, and its transformation rate is the slowest, and the slow growth process of pearlite lamellae can be observed.
[0072] Furthermore, the phase transformation type described in the present invention is alloy solid / liquid phase and / or alloy microstructure phase.
[0073] Specifically, when the low alloy steel is heated to a temperature above the melting point in step (2), the low alloy steel undergoes a transformation from a solid state to a liquid state. The high temperature metallographic microscope system of the present invention can accurately determine the melting point of the low alloy steel, that is, the temperature when the steel is heated to a point where a liquid phase appears in the field of view of the microscope is the melting point temperature. During the continuous cooling process, a transformation from a liquid state to a solid state occurs. The high temperature metallographic microscope system of the present invention can accurately determine the solidification point of the low alloy steel, that is, the temperature when the steel is cooled to a point where solid phase nucleation appears in the field of view of the microscope is the solidification point temperature.
[0074] Specifically, the alloy microstructure phase is the alloy transformation product structure in the continuous cooling process of the present invention. Depending on the cooling rate, the alloy transformation product structure is one or more of pearlite, bainite, and martensite.
[0075] Specifically, the present invention uses Adobe Premiere Pro video processing software to import video image data, and observes the sample video images obtained from the experiment frame by frame with the naked eye. When the solid-state phase transition temperature of low-alloy steel is determined, the temperature is based on the first phase transition structure appearing in the field of view, and this temperature is the phase transition starting temperature. When no new phase transition structure appears in the field of view, this temperature is the phase transition termination temperature.
[0076] It should be noted that in order to improve accuracy, the present invention can use the same low-alloy steel sample to perform 2-5 groups of parallel experiments: the sample is heated to above the austenitizing temperature at the same heating rate and heating method, and maintained for the same time; the material is cooled and solidified at the same continuous cooling rate; the collected images are processed in the same way, and finally the average value is taken. It is found that: the repeatability of multiple groups of parallel experiments is good, such as the repeatability of the specific microstructure phase transformation starting temperature obtained is good, and fluctuates within the range of ±1°C, which shows that the reliability of the technical solution of the present invention is high.
[0077] Furthermore, in terms of mass percentage, the composition of the low alloy steel includes: C 0.05-0.25%, Si 0.15-0.5%, Mn 0.3-1.5%, Cu<0.05%, Ni 0.25-1.0%, Cr0.25-1%, Nb 0.02-0.15%, V 0.02-0.15%, Al<0.1%, Ti 0.02-0.15%, Mo 0.15-0.5%, B<0.003%, P<0.015%, S<0.015%, N<0.025%, and the rest is Fe.
[0078] According to a preferred embodiment of the present invention, calculated by mass percentage, when the composition of the low alloy steel (Q890D) is C 0.11%, Si 0.24%, Mn 1.26%, Cu 0.018%, Ni 0.28%, Cr 0.33%, Nb 0.03%, V0.048%, Al 0.024%, Ti 0.014%, Mo 0.5%, B0.0012%, P 0.013%, S 0.0035%, N0.0037%, and the remainder is Fe. For example, when the cooling rate is 10℃ / s, it transforms into a martensite structure with a starting temperature of 424.5℃ and an ending temperature of 321.0℃; when the cooling rate is 0.3℃ / s, it transforms into a mixed structure of bainite and martensite with a starting temperature of 451.1℃ and an ending temperature of 352.0℃; when the cooling rate is 0.05℃ / s, it transforms into a mixed structure of pearlite, ferrite and bainite with a starting temperature of 709.4℃ and an ending temperature of 630.0℃; when the sample is heated at a heating rate of 5℃ / s until it is completely melted and kept warm for an appropriate time, and then slowly cooled at a cooling rate of 0.05℃ / s, the melting point is measured to be 1352℃ and the solidification point is 1407℃.
[0079] In addition, through data analysis technology, the results of the continuous cooling experiment were statistically analyzed to obtain the CCT curve of low alloy steel under a constant continuous cooling rate; multiple groups of identical specimens were continuously cooled at a constant rate, and the cooling rates of each group of specimens were different, namely 20℃ / s, 10℃ / s, 5℃ / s, 1℃ / s, 0.3℃ / s, 0.15℃ / s, 0.1℃ / s, 0.05℃ / s, and 0.03℃ / s, and multiple groups of parallel experiments were performed. According to the results of multiple groups of experiments, the continuous cooling transformation phase diagram of low alloy steel can be obtained, thereby obtaining the change of phase change temperature with the continuous cooling rate during the continuous cooling process.
[0080] It should be noted that the results obtained after the organizational analysis (phase change type and phase change degree) are matched with the alloy performance test results to more accurately evaluate the heat treatment effect, reasonably select the heat treatment processing temperature to optimize the heat treatment process, or guide the design of new materials that meet special environmental and performance requirements.
[0081] Specifically, the method of the present invention further comprises conducting mechanical property tests on the sample after the continuous cooling treatment in step (3), including strength, plasticity, hardness, elasticity, etc.
[0082] According to a preferred embodiment of the present invention, the present invention performs a hardness test on the sample after subsequent cooling treatment.
[0083] The present invention also provides a method for regulating the mechanical properties of low alloy steel, and the method comprises the above method for measuring the continuous cooling phase transition temperature of low alloy steel.
[0084] The method for determining the continuous cooling phase transition temperature of low alloy steel of the present invention is used to study the phase transition process of low alloy steel, so that the visualization and accurate measurement of the continuous cooling phase transition temperature of low alloy steel are realized. By collecting the dynamic changes of the phase transition type and the phase transition degree during the continuous cooling process, the CCT curve of the low alloy steel is obtained, and the continuous cooling phase transition process is accurately controlled. The sample organization analysis results (phase transition type and phase transition degree) are matched with the sample performance, so that the heat treatment effect can be better evaluated and the heat treatment process can be optimized.
[0085] In terms of performance control, we can understand the influence of factors such as phase change temperature and time on the performance of steel. For example, by controlling the cooling rate to change the phase change process, different organizations can be obtained. For example, bainite organization can make steel have good strength and toughness, which helps to produce steel that meets specific strength and toughness requirements for use in building structures, machinery manufacturing and other industries. In terms of processing technology optimization, knowing the phase change law can optimize the hot working process. For example, when forging or rolling, the processing temperature range can be reasonably selected according to the phase change temperature of low alloy steel to avoid defects such as cracks in steel caused by processing in the temperature range sensitive to phase change, thereby improving product quality and yield rate; in the field of new material development, studying the phase change of low alloy steel can provide a theoretical basis for the development of new high-performance low alloy steel, and can design materials that are more suitable for special environments and performance requirements. Therefore, this technical solution has a broad market demand and has great application potential in the fields of metal material research and development, quality control, etc.
[0086] It should be noted that the method of the present invention can be expanded to realize the visualization and precise measurement of the phase change temperature of other metals or alloys during heat treatment, as well as the collection of dynamic changes in the type and degree of heat treatment phase change, to optimize the heat treatment process of metals or alloys and realize the regulation of material properties.
[0087] The technical solution of the present invention is further explained below in conjunction with specific embodiments.
[0088] The composition of the low alloy steel (Q890D) used in Examples 1-10 of the present invention is calculated by mass percentage, and the composition is C 0.11%, Si 0.24%, Mn 1.26%, Cu 0.018%, Ni 0.28%, Cr 0.33%, Nb 0.03%, V0.048%, Al 0.024%, Ti 0.014%, Mo 0.5%, B0.0012%, P 0.013%, S 0.0035%, N0.0037%, and the balance is Fe.
[0089] In Examples 1-10, before the samples are heat treated, the preparation and loading process of the low alloy steel samples are the same, specifically:
[0090] (1) Cut low alloy steel Q890D into A small cylinder is used to grind and polish any plane to ensure that the sample is clean and free of contamination; in the embodiment of measuring the melting and / or solidification temperature of the sample, a micro Vickers hardness tester is required to accurately locate the center of the sample and make hardness marking points;
[0091] (2) Place the sample in a crucible, ensure that the sample is at an appropriate height, and place it in the heating furnace of a high-temperature laser confocal microscope system, and align the laser of the microscope with the center of the sample or the hardness mark of the sample;
[0092] The high-temperature laser confocal microscope system was vacuumed and supplied with protective gas for three times. Each vacuuming and supplying took three minutes. The argon flow rate was 200CC and the helium flow rate was 6000CC. A low-power objective was used for observation. The image was adjusted to make the picture clear. The number of image acquisition was set to 5 frames per second.
[0093] Example 1
[0094] (3) Setting up the experimental program, heating the sample to 1540°C at a heating rate of 5°C / s and keeping it at that temperature for 10 min to completely melt the low alloy steel I, and then slowly cooling it at a cooling rate of 0.05°C / s. During the experiment, the sample video images collected in situ were recorded and saved in real time, with a magnification of 500 times;
[0095] (4) Observe the sample video images obtained by the experiment frame by frame. The temperature when the liquid phase appears in the field of view is 1352.0℃, which is the melting point of low alloy steel I. Figure 1 (a) shows that the temperature when solid phase nucleation appears in the cooling process field is 1407.5℃, which is the solidification temperature of low alloy steel I. Figure 1 (b)
[0096] Image Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method combined with manual calibration to obtain the following: Figure 1 The solid-liquid two-phase distribution diagram of low alloy steel I and its solid phase percentage during the heating and cooling process of heat treatment are shown.
[0097] Example 2
[0098] (3) Setting up the experimental procedure, first preheating the equipment heating furnace to 200°C at 1.5°C / s, then heating to 975°C at 5°C / s, and keeping it at that temperature for 15 minutes, so that the alloy structure is completely transformed into austenite; then cooling at a rate of 20°C / s to room temperature, using helium as the cooling gas; during the experiment, real-time recording and saving of sample video images collected in situ, with a magnification of 1000 times;
[0099] (4) By observing the sample video images obtained from the experiment frame by frame, it was found that when the temperature was cooled to 425.1℃, the first martensitic phase transformation structure appeared in the field of view, indicating that the martensitic phase transformation starting temperature of low alloy steel I was 425.1℃ during the cooling process at a rate of 20℃ / s; when cooled to 321.2℃, no new martensitic phase transformation structure appeared in the field of view, and the martensitic phase transformation end temperature was 321℃, which was consistent with the thermodynamic calculation value;
[0100] Adobe Premiere Pro image processing software was used to import image data, and the percentage of each phase was calculated by combining the binary method with the manual calibration method. Figure 2 The martensitic microstructure distribution diagram and its percentage of low alloy steel I during the continuous cooling process are shown in the figure, and a CCT curve is made, such as Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 20℃ / s, the alloy martensite structure is finally obtained;
[0101] During the continuous cooling process of Example 2, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 388 (HV5kg).
[0102] Example 3
[0103] The same method as in Example 2 was used, except that the cooling rate in step (3) was 1°C / s, and helium was used as the cooling gas; during the experiment, the sample video images collected in situ were recorded and saved in real time;
[0104] By observing the sample video images obtained from the experiment frame by frame, it is found that when the temperature is cooled to 424.5℃, the first martensitic phase transformation structure appears in the field of view, indicating that the martensitic phase transformation starting temperature of low alloy steel I is 424.5℃ during the cooling process at a rate of 10℃ / s; when cooled to 321.0℃, no new martensitic phase transformation structure appears in the field of view, and the martensitic phase transformation end temperature is 321.0℃, which is consistent with the thermodynamic calculation value;
[0105] Adobe Premiere Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method and manual calibration method. Figure 3 The martensitic microstructure distribution diagram and its percentage of low alloy steel I during the continuous cooling process are shown in the figure, and a CCT curve is made, such as Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 10℃ / s, the alloy martensite structure is finally obtained;
[0106] During the continuous cooling process of Example 3, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 379 (HV5kg).
[0107] Example 4
[0108] The same method as in Example 2 was used, except that the cooling rate in step (3) was 5°C / s, and argon gas was used as the cooling gas; during the experiment, the sample video images collected in situ were recorded and saved in real time;
[0109] By observing the sample video images obtained from the experiment frame by frame, it is found that when the temperature is cooled to 425.5℃, the first martensitic phase transformation structure appears in the field of view, indicating that the martensitic phase transformation starting temperature of low alloy steel I is 425.5℃ during the cooling process at a rate of 5℃ / s; when cooled to 321.2℃, no new martensitic phase transformation structure appears in the field of view, and the martensitic phase transformation end temperature is 321.2℃, which is consistent with the thermodynamic calculation value;
[0110] Adobe Premiere Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method and manual calibration method. Figure 4 The martensitic microstructure distribution diagram and its percentage of low alloy steel I during the continuous cooling process are shown in the figure, and a CCT curve is made, such as Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 5℃ / s, the alloy martensitic structure is finally obtained.
[0111] During the continuous cooling process of Example 4, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 381 (HV5kg).
[0112] Example 5
[0113] The same method as in Example 2 was used, except that the cooling rate in step (3) was 1°C / s, and argon gas was used as the cooling gas; during the experiment, the sample video images collected in situ were recorded and saved in real time;
[0114] By observing the sample video images obtained by the experiment frame by frame, it is found that when the temperature is cooled to 425.2℃, the first martensitic phase transformation structure appears in the field of view, indicating that the martensitic phase transformation starting temperature of low alloy steel I is 425.2℃ during the cooling process at a rate of 1℃ / s; when cooled to 321.1℃, no new martensitic phase transformation structure appears in the field of view, and the martensitic phase transformation end temperature is 321.1℃, which is consistent with the thermodynamic calculation value;
[0115] Adobe Premiere Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method and manual calibration method. Figure 5 The martensitic microstructure distribution diagram and its percentage of low alloy steel I during the continuous cooling process are shown in the figure, and a CCT curve is made, such as Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 1°C / s, the alloy martensite structure is finally obtained;
[0116] During the continuous cooling process of Example 5, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 374 (HV5kg).
[0117] Example 6
[0118] The same method as in Example 2 was used, except that the cooling rate in step (3) was 0.3°C / s, and argon gas was used as the cooling gas; during the experiment, the sample video images collected in situ were recorded and saved in real time;
[0119] By observing the sample video images obtained from the experiment frame by frame, it is found that when the temperature is cooled to 451.1℃, the first bainite phase transformation structure appears in the field of view, indicating that the starting temperature of the bainite phase transformation of low alloy steel I is 451.1℃ during the cooling process at a rate of 0.3℃ / s; when cooled to 352.0℃, no new bainite phase transformation structure appears in the field of view, and the end temperature of the bainite phase transformation is 352.0℃, which is consistent with the thermodynamic calculation value;
[0120] Image Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method and manual calibration method to obtain the following: Figure 6 The bainite microstructure phase distribution diagram and its percentage content of low alloy steel I during the continuous cooling process are shown in the figure, and the CCT curve is made, as shown in the figure. Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 0.3℃ / s, a mixed structure of alloy bainite and martensite is finally obtained;
[0121] During the continuous cooling process of Example 6, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 355 (HV5kg).
[0122] Example 7
[0123] The same method as in Example 2 was used, except that the cooling rate in step (3) was 0.15°C / s, and argon gas was used as the cooling gas; during the experiment, the sample video images collected in situ were recorded and saved in real time;
[0124] By observing the sample video images obtained by the experiment frame by frame, it is found that when the temperature is cooled to 498.5℃, the first bainite phase transformation structure appears in the field of view, indicating that the starting temperature of the bainite phase transformation of low alloy steel I is 498.5℃ during the cooling process at a rate of 0.15℃ / s; when cooled to 368.4℃, no new bainite phase transformation structure appears in the field of view, and the end temperature of the martensite phase transformation is 368.4℃, which is consistent with the thermodynamic calculation value;
[0125] Image Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method and manual calibration method to obtain the following: Figure 7 The bainite and martensite mixed microstructure phase distribution diagram and its percentage content of low alloy steel I during the continuous cooling process are shown in the figure, and the CCT curve is made, as shown in the figure. Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 0.15℃ / s, a mixed structure of alloy bainite and martensite is finally obtained;
[0126] During the continuous cooling process of Example 7, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 323 (HV5kg).
[0127] Example 8
[0128] The same method as in Example 2 was used, except that the cooling rate in step (3) was 0.1°C / s, and argon gas was used as the cooling gas; during the experiment, the sample video images collected in situ were recorded and saved in real time;
[0129] By observing the sample video images obtained by the experiment frame by frame, it is found that when the temperature is cooled to 670.4℃, the first pearlite phase transformation structure appears in the field of view, indicating that the starting temperature of the pearlite phase transformation of low alloy steel I is 670.4℃ during the cooling process at a rate of 0.1℃ / s; when cooled to 330.4℃, no new bainite phase transformation structure appears in the field of view, and the end temperature of the bainite phase transformation is 321.1℃, which is consistent with the thermodynamic calculation value;
[0130] Image Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method and manual calibration method to obtain the following: Figure 8 The pearlite, ferrite and bainite mixed microstructure phase distribution diagram and their percentage content of low alloy steel I during the continuous cooling process are shown in the figure, and the CCT curve is made, as shown in the figure. Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 0.1℃ / s, a mixed structure of alloy pearlite and bainite is finally obtained;
[0131] During the continuous cooling process of Example 8, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 292 (HV5kg).
[0132] Example 9
[0133] The same method as in Example 2 was used, except that the cooling rate in step (3) was 0.05°C / s, and argon gas was used as the cooling gas; during the experiment, the sample video images collected in situ were recorded and saved in real time;
[0134] By observing the sample video images obtained by the experiment frame by frame, it is found that when the temperature is cooled to 709.4℃, the first pearlite phase transformation structure appears in the field of view, indicating that the starting temperature of the pearlite phase transformation of low alloy steel I is 709.4℃ during the cooling process at a rate of 0.05℃ / s; when cooled to 322.1℃, no new bainite phase transformation structure appears in the field of view, and the end temperature of the bainite phase transformation is 322.1℃, which is consistent with the thermodynamic calculation value;
[0135] Image Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method and manual calibration method to obtain the following: Fig. 9 The pearlite, ferrite and bainite mixed microstructure phase distribution diagram and their percentage content of low alloy steel I during the continuous cooling process are shown in the figure, and the CCT curve is made, as shown in the figure. Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 0.05℃ / s, a mixed structure of alloy pearlite, ferrite and bainite is finally obtained.
[0136] During the continuous cooling process of Example 9, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 256 (HV5kg).
[0137] Example 10
[0138] The same method as in Example 2 was used, except that the cooling rate in step (3) was 0.03°C / s, and argon gas was used as the cooling gas; during the experiment, the sample video images collected in situ were recorded and saved in real time;
[0139] By observing the sample video images obtained by the experiment frame by frame, it is found that when the temperature is cooled to 720.1℃, the first pearlite phase transformation structure appears in the field of view, indicating that the starting temperature of the pearlite phase transformation of low alloy steel I is 720.1℃ during the cooling process at a rate of 0.05℃ / s; when cooled to 320.7℃, no new bainite phase transformation structure appears in the field of view, and the end temperature of the bainite phase transformation is 320.7℃, which is consistent with the thermodynamic calculation value;
[0140] Image Pro image processing software was used to import image data, and the percentage of each phase was calculated by binary method and manual calibration method to obtain the following: Fig.10 The pearlite, ferrite and bainite mixed microstructure phase distribution diagram and their percentage content of low alloy steel I during the continuous cooling process are shown in the figure, and the CCT curve is made, as shown in the figure. Fig.11 As shown in the figure, it can be seen that when the low alloy steel Q890D is continuously cooled at a cooling rate of 0.03℃ / s, a mixed structure of alloy pearlite, ferrite and bainite is finally obtained;
[0141] During the continuous cooling process of Example 10, the mechanical properties of the low alloy steel sample obtained by continuous cooling were measured by a hardness method, and the Vickers hardness value was 259 (HV5kg).
[0142] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for determining the continuous cooling phase transition temperature of low alloy steel, characterized in that: The method comprises: (1) Preparation of low alloy steel samples; (2) placing the sample in a heating device of a high-temperature metallographic microscope system for heating treatment and in-situ observation; (3) subjecting the sample to continuous cooling treatment and in-situ observation; (4) Importing the images collected in step (2) and step (3) into the software, the phase change type and the percentage of each phase are obtained by binary method and calibration method.
2. The method according to claim 1, characterized in that In step (2), the specific steps of the temperature-raising heat treatment are: raising the temperature of the sample to above the austenitizing temperature and maintaining the temperature, and the heating rate is 1-20°C / s.
3. The method according to claim 1, characterized in that In step (2), the magnification of the high temperature metallographic microscope is 250-2000 times, the image acquisition resolution is 1024*1024 pixels, and the image acquisition number is 1-50 frames / second.
4. The method according to claim 1, characterized in that: In step (2), before subjecting the sample to a temperature-raising heat treatment, the method further includes: introducing argon and helium into the high-temperature metallographic microscope system and evacuating the system, and performing a cycle of 3-5 times.
5. The method according to claim 1, characterized in that In step (3), the continuous cooling temperature is 0.03-100°C / s.
6. The method according to claim 1, characterized in that In step (1), the sample preparation method includes: processing a low alloy steel cylindrical sample, grinding, polishing, cleaning and drying.
7. The method according to claim 1, characterized in that In step (4), the phase change type is alloy solid / liquid phase, Or / and, alloy microstructure phase; the alloy microstructure phase is one or more of pearlite, bainite and martensite.
8. The method according to claim 1, characterized in that The method further comprises conducting a mechanical property test on the sample after the continuous cooling treatment in step (3).
9. The method according to claim 1, characterized in that: The composition of the low alloy steel includes, by mass percentage, C 0.05-0.25%, Si 0.15-0.5%, Mn 0.3-1.5%, Cu<0.05%, Ni 0.25-1.0%, Cr 0.25-1%, Nb 0.02-0.15%, V 0.02-0.15%, Al<0.1%, Ti 0.02-0.15%, Mo 0.15-0.5%, B<0.003%, P<0.015%, S<0.015%, N<0.025%, and the rest is Fe.
10. A method for regulating the mechanical properties of low alloy steel, characterized in that: The control method comprises the method according to any one of claims 1 to 9.